45‐3: Late‐News Paper: Homogeneous Alignment LCDs Could be Prime Candidate for Multiple Scene Interactive Interface and Devices. Issue 1 (25th September 2020) - Yang, Ruizhi; You, Yang; Wu, Jun; Ma, Shiqing; Yan, Guang; Shi, Guangdong; Qu, Lianjie; Xu, Xiaoling; Zhao, Hebin; Qiu, Yun; Wang, Dan
Abstract : When more and more display devices are used as interaction interface, touch has been essential function integrated in display devices. Homogeneous alignment LCDs and full in cell touch technology has been developed and applied on mobile phone, tablet PC, notebook PC, Monitor and even TV scale. In this paper, we made a comparison on different display technology in the point of not only display specification but also human experience. ADS type homogeneous alignment LCDs would keep its major position in small and middle size market and expand share on big size in furtherfollowing the development of interaction devices.